Mortar for improving overall performance based on fine coal gasification slag and preparation method thereof

A controlled mortar composition with coal gasification fine slag enhances mortar performance by optimizing hydration products and mechanical properties, achieving optimal results with a 30% slag content.

CN119191786APending Publication Date: 2024-12-27TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411287127.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing mortars using coal gasification fine slag do not consider the comprehensive properties of the mortar as a whole, leading to defects in certain properties such as fluidity, setting time, and mechanical strength.

Method used

A mortar composition comprising 11-20wt% cement, 58-75.8wt% standard sand, and 2.2-11.1wt% coal gasification fine slag, with controlled addition and preparation methods to enhance hydration product content and mechanical properties.

Benefits of technology

The solution effectively increases hydration product content, improves fluidity and setting time, and maintains mechanical strength, with optimal performance achieved at a coal gasification fine slag content of 30%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191786A_ABST
    Figure CN119191786A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and discloses mortar for improving overall performance based on fine coal gasification slag and a preparation method of the mortar. The mortar is prepared from the following components in percentage by mass: 11 to 20 weight percent of cement, 58 to 75.8 weight percent of standard sand and 2.2 to 11.1 weight percent of coal gasification fine slag; screening the fine coal gasification slag, diluting the fine coal gasification slag with other raw materials by adding water, and stirring to prepare fine coal gasification slag slurry; fully stirring the coal gasification fine slag slurry, introducing the coal gasification fine slag slurry into a screening device, screening the coal gasification fine slag slurry through a 200-400-mesh sieve to separate out large-particle solid components, and collecting undersize separation slurry to obtain composite slurry; according to the method, the mixing amount of the coal gasification fine slag for replacing part of cement and the parameters of the method are accurately controlled, the content of hydration products in the neat paste is effectively increased finally, and meanwhile, the content of CSH gel in the system is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials and relates to a mortar with improved overall performance based on coal gasification fine slag and a preparation method thereof. Background Art

[0002] Coal gasification slag is a solid waste produced in the process of coal gasification, which has certain physical and chemical properties. It is used as an auxiliary cementitious material in mortar to improve the performance of mortar, such as its strength, durability and impermeability.

[0003] Coal gasification is a process that converts coal or other solid fuels into synthesis gas (mainly carbon monoxide, hydrogen and carbon dioxide). The fine slag produced in this process is usually rich in mineral components such as silicon, aluminum, and iron, which can be used as a cementitious material. Cementitious materials (such as cement) undergo hydration reactions in water to form a solid structure and combine with other aggregates to improve the strength and stability of mortar. Adding auxiliary cementitious materials can improve the performance of mortar, reduce costs, and reduce the amount of cement. Coal gasification fine slag has a high specific surface area, which helps to improve the fluidity and workability of mortar. At the same time, the chemical composition of the fine slag can react with the components in cement to form additional hydration products, thereby enhancing the comprehensive performance of mortar.

[0004] Using coal gasification slag as an auxiliary cementitious material can not only effectively utilize industrial waste and reduce environmental pollution, but also reduce energy consumption in the mortar production process. In recent years, more and more studies have shown that the addition of coal gasification slag can improve the mechanical properties, durability and frost resistance of mortar and promote the sustainable development of mortar. Therefore, using coal gasification slag as an auxiliary cementitious material to improve mortar performance is a technological innovation and environmentally friendly application with good development prospects.

[0005] However, the prior art controls the amount and method of adding coal gasification slag to replace a portion of the cementitious material in a relatively rough manner, and the mortar with added coal gasification slag often only focuses on the improvement effect of its individual properties, without considering the changes in the comprehensive properties of the mortar as a whole, resulting in defects in certain properties of the mortar. Summary of the invention

[0006] The present invention overcomes the shortcomings of the prior art and provides a mortar with improved overall performance based on coal gasification fine slag and a preparation method thereof.

[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions.

[0008] A mortar with improved overall performance based on coal gasification fine slag comprises 11-20wt% of cement, 58-75.8wt% of standard sand and 2.2-11.1wt% of coal gasification fine slag.

[0009] Preferably, the mass percentage content of coal gasification fine slag carbon is 23.41%.

[0010] Preferably, the cement is silicate PI42.5 benchmark cement.

[0011] A method for preparing mortar with improved overall performance based on coal gasification fine slag comprises the following steps: S1. Treatment of coal gasification fine slag: Dry the coal gasification fine slag at 100-110°C to constant weight, and sieve it using a 180-200 mesh sieve; S2. Weigh 2.2-11.1wt% of coal gasification slag, add 11-20wt% of cement, 58-75.8wt% of standard sand and water to dilute and stir to form a coal gasification slag slurry with a solid mass fraction of 88-89wt%; the coal gasification slag, standard sand and cement are all amorphous, and the particle size is less than 110μm; S3. The coal gasification fine slag slurry is fully stirred and introduced into a screening device, and the large-particle solid components are separated through a 200-400 mesh sieve, and the separated slurry under the sieve is collected to obtain a composite slurry.

[0012] Preferably, the stirring in step S2 is carried out at room temperature using a high-speed disperser, with a stirring speed of ≥1500 r / min and a stirring time of ≥30 min.

[0013] More preferably, the stirring time in step S2 is ≥ 1.5 h.

[0014] Preferably, the rotation speed of the sufficient stirring in step S3 is 1800-3000 r / min, and the stirring time is 30-120 min.

[0015] The beneficial effects of the present invention compared with the prior art are as follows: The present invention comprehensively considers the setting time, fluidity and mechanical properties of the composite mortar, and analyzes the hydration mechanism of the coal gasification slag-cement composite cementitious material in combination with hydration heat, XRD, scanning electron microscopy and thermodynamic simulation, accurately controls the dosage of the coal gasification slag to replace part of the cement and the method parameters, and ultimately effectively increases the content of hydration products in the neat slurry, while increasing the content of CSH gel in the system. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a particle size distribution curve diagram of the raw material of the present invention; Figure 2 is the XRD pattern of the raw material of the present invention; Figure 3 It is the fluidity diagram of the mortar of the present invention; Figure 4 This is a graph showing the setting time of the pure slurry of the present invention; Figure 5 This is the flexural strength diagram of the mortar of the present invention; Figure 6 is the compressive strength diagram of the mortar of the present invention; Figure 7 The heat release rate and cumulative heat release curve of the cement paste of the present invention; Figure 8 This is a graph showing the reaction rate curve fitting results of the cement paste of the present invention; Fig. 9 XRD patterns of C0 and C2 after curing for 3 d and 28 d in the present invention; Fig.10 The SEM images of C0 and C2 of the present invention after curing for 28 days; Fig.11 This is a thermodynamic simulation diagram of the effect of the amount of coal gasification fine slag added on the hydration products of the clean slurry in the present invention. DETAILED DESCRIPTION

[0017] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail in conjunction with the embodiments and the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The technical solutions of the present invention are described in detail below in conjunction with the embodiments and the accompanying drawings, but the scope of protection is not limited thereto.

[0018] Example 1 This embodiment proposes a mortar based on coal gasification slag to improve overall performance and a preparation method thereof, wherein the mortar includes the following raw materials by mass fraction: 1350g of standard sand, 405g of cement, and 45g of coal gasification slag (replacing 10% of cement). The cement is silicate PI42.5 standard cement, the coal gasification slag comes from a chemical company in Shanxi, the standard sand used is standard sand produced by Xiamen AISIO Standard Sand Company, the mixing water is ordinary tap water, and the chemical composition of the raw materials is shown in Table 1. The particle size distribution curve of the raw materials is shown in Figure 1 , the XRD patterns of the raw materials are as follows Figure 2 , the mass percentage of mineral components of raw materials is shown in Table 2; A method for preparing mortar with improved overall performance based on coal gasification fine slag comprises the following steps: S1. Treatment of coal gasification fine slag: Dry the coal gasification fine slag at 110°C to constant weight, and sieve it using a 180-200 mesh sieve; S2. Weigh the coal gasification fine slag according to the above weight, add cement, standard sand and 225g of water to dilute and stir to form a solid coal gasification fine slag slurry; the coal gasification fine slag, standard sand and cement are all amorphous, and the particle size is less than 110μm; the stirring is carried out at room temperature using a high-speed disperser, the stirring speed is 1500r / min, and the stirring time is 1.5h.

[0019] S3, after fully stirring the coal gasification fine slag slurry, introduce it into the screening device, separate the large particle solid components through a 400 mesh sieve, and collect the separated slurry under the sieve to obtain the composite slurry. The speed of the fully stirring is 3000r / min, and the stirring time is 120min. The prepared mortar is numbered C1.

[0020] Example 2 This embodiment proposes a mortar with improved overall performance based on coal gasification slag and a preparation method thereof, wherein the mortar comprises the following raw materials by mass fraction: 1350 g of standard sand, 315 g of cement, and 135 g of coal gasification slag (replacing 30% of cement). The rest is the same as in Example 1. The prepared mortar is numbered C2.

[0021] Example 3 This embodiment proposes a mortar with improved overall performance based on coal gasification slag and a preparation method thereof, wherein the mortar comprises the following raw materials by mass fraction: 1350 g of standard sand, 225 g of cement, and 225 g of coal gasification slag (replacing 50% of cement). The rest is the same as in Example 1. The prepared mortar is numbered C3.

[0022] Comparative Example 1 A mortar, raw materials: 1350g of standard sand and 450g of cement, without using coal gasification fine slag. The rest is the same as Example 1. The prepared mortar is numbered C0.

[0023] Performance testing: The mortars prepared in Examples 1-3 and Comparative Example 1 were tested for performance; the fluidity, setting time and mechanical properties of the mortars were tested at ages of 3d, 7d, 14d and 28d; The cement paste blocks that have reached the curing age were broken and soaked in isopropanol for 12-13 hours with an isopropanol concentration of 10%. The samples were then dried at 40-45°C. Some of the samples were further ground and passed through a 200-300 mesh sieve for XRD analysis; another block sample was used for SEM testing. The composition of the samples is shown in Table 3: In the performance study (fluidity, setting time and mechanical properties) of mortar of the present invention, four groups of experiments are set up, namely C0, C1, C2 and C3, the percentages of cement replaced by coal gasification fine slag are 10%, 30% and 50% respectively, the temperature microcalorimeter used is a TAMAir eight-channel isothermal microcalorimeter, the time for measuring the hydration heat release rate and heat release of the composite cement slurry is 72 hours, the time for soaking the cement slurry block in isopropanol is 12 hours, the time for drying the sample is 40°C, some samples are further ground and passed through a sieve of 200 mesh, the equipment used for XRD test is a SmartLab 3kw X-ray diffractometer (Japan Rigaku Co., Ltd.) to collect the XRD spectrum of the sample in the range of 5-50°2θ at a scanning rate of 5° / min, and the SEM test equipment used for another block sample is a Gemini 300 of German Zeiss Company.

[0024] 1. Study on the fluidity of mortar Four groups of experiments were set up, of which the last three groups (C1-C3) were coal gasification slag-cement test groups, in which coal gasification slag replaced different percentages of cement, and C0 was a pure cement control group. The flow properties of the mortar were observed after adding coal gasification slag. The fluidity of the mortar was as follows: Figure 3 The addition of coal gasification slag significantly reduced the fluidity of the mortar. The fluidity of C1, C2, and C3 decreased by 27.71%, 52.96%, and 61.03% respectively compared with C0. This is because there are a large number of porous carbons with large specific surface areas in the coal gasification slag. These porous carbons adsorb a large amount of free water, resulting in a decrease in the free water content in the mortar that can be used for lubrication. In addition, the coal gasification slag also contains a large amount of organic matter, which increases the viscosity of water in the mortar. Therefore, as the content of coal gasification fines increases, the fluidity of the mortar decreases significantly.

[0025] 2. Study on the setting time of mortar Add coal gasification slag to observe and calculate the setting time of the pure slurry. According to the influence of cement replaced by coal gasification slag, the reasons for the length of setting time are analyzed. Figure 4The addition of coal gasification slag prolongs the setting time of the paste. The initial setting time of C1, C2, and C3 increases by 4.61%, 14.47%, and 25.33% respectively compared with C0, and the final setting time increases by 6.14%, 15.50%, and 30.07% respectively. Since the hardening of the early paste mainly depends on cement hydration, the cement is diluted after the coal gasification slag replaces the cement, so the setting time of the paste increases. The 10% addition of coal gasification slag has little effect on the setting time of the paste. This is because the amount of coal gasification slag is small, and the coal gasification slag absorbs a large amount of free water, which reduces the "effective water-cement ratio" in the paste, which can accelerate the setting of cement. As the content of coal gasification slag increases further, the cement is further diluted, and the organic matter in it will also inhibit cement hydration, so the setting time of the paste is significantly extended.

[0026] 3. Study on the mechanical properties of mortar The four groups of samples were cured for a period of time. The cement paste blocks that reached the curing age were broken and soaked in isopropanol. The samples were then dried. Some of the samples were further ground and sieved for XRD analysis. Another part of the block samples was used for SEM testing to analyze the flexural strength and compressive strength of the mortar at a specific age. The flexural strength of the mortar was as follows: Figure 5 , mortar compressive strength Figure 6 , analyze the relationship between mortar strength and cement hydration; With the increase of curing age, the flexural strength of mortar gradually increases; but with the increase of coal gasification fine slag content, the flexural strength of mortar gradually decreases. The flexural strength of C1 decreased by 3.9%~8.0% compared with C0; the flexural strength of C2 decreased by 25.4%~27.3% compared with C0, and the decline was significantly larger; the flexural strength of C3 decreased by 45.4%~54.3% compared with C0, and the decline was even more than 50%.

[0027] Similar to the flexural strength, the compressive strength of the mortar gradually increases with the increase of curing age; and the compressive strength of the mortar gradually decreases with the increase of the amount of coal gasification fine slag. The difference is that with the increase of curing age, the compressive strength of C1 is very close to C0. At 3d, the compressive strength of C1 decreased the most compared with C0, reaching 12.42%; after 28 days of curing, the difference between the two was only 0.3%. The compressive strength of C2 decreased by 24.3%~29.4% compared with C0; the compressive strength of C3 decreased by 47.6%~60.5% compared with C0. It can be seen that the high-parameter coal gasification fine slag has a more significant effect on the compressive strength of the mortar.

[0028] In the early stage of hydration, the strength development of mortar is mainly related to cement hydration. The use of coal gasification slag to replace cement leads to cement dilution, so the early mechanical properties of mortar decrease more significantly. With the extension of curing time, the amorphous phase in the coal gasification slag gradually reacts with the calcium hydroxide formed by cement hydration to form additional hydration products, which compensates for the adverse effects of cement dilution and organic matter inhibition of hydration, thereby reducing the gap between the experimental group and the control group. In addition, the particle size and specific surface area of ​​coal gasification slag are larger than those of cement particles, which can play a certain physical filling and nucleation role. Therefore, when the coal gasification slag content is 10%, the mortar strength after 28 days of curing is equivalent to that of pure cement. However, due to the poor activity of the amorphous phase in the coal gasification slag, when its content exceeds 10%, the volcanic ash reaction, filling and nucleation effects cannot compensate for the amplitude effect caused by cement dilution. It can be seen that the content of coal gasification slag in cement should not exceed 10%.

[0029] 4. Analysis of the hydration mechanism of coal gasification slag-cement composite cementitious materials The heat release rate and heat release of the composite cement paste after hydration for a certain period of time were measured using an isothermal microcalorimeter. The heat release rate and cumulative heat release of the paste were recorded. The heat release rate and cumulative heat release curve of the cement paste were as follows: Figure 7 The reaction rate curve fitting results of cement paste are as follows: Figure 8 The reasons for the speed of heat release rate and the cumulative heat release of the paste with the increase of coal gasification slag content are analyzed. The hydration process of the paste is further analyzed by using the Krstulovic-Dabic hydration kinetic model combined with the hydration heat data. The hydration process is divided into three stages: nucleation and crystal growth (NG), phase interface (I) and diffusion (D). The hydration rate curve of the paste and the simulation results are used to analyze the hydration behavior of the paste under high content of coal gasification fine slag and the performance of pure cement. According to the hydration kinetic parameters of the paste (n, K NG ', K I ', K D '), the hydration kinetic parameters of cement paste are shown in Table 4, the relationship between the amount of coal gasification fine slag and the nucleation and crystal growth of hydration products is analyzed, the relationship between the amount of coal gasification fine slag and the phase interface (I) and diffusion (D) is analyzed, and the reason for the poor early mechanical properties of mortar is analyzed. XRD test analysis is carried out on C0 and C2 samples. The XRD spectra of C0 and C2 after curing for 3d and 28d are shown in Fig. 9 The main hydration products in the slurry were obtained. The SEM images of C0 and C2 after 28 days of curing were analyzed. The SEM images of C0 and C2 after 28 days of curing are shown in Figure 2. Fig.10, analyze the relationship between more pores and cracks and poor mechanical properties of mortar with high coal gasification fine slag content, use GMES software to analyze the hydration products of the paste, and gain a deeper understanding of the effect of coal gasification fine slag content on the hydration products of cement paste. The thermodynamic simulation of the effect of coal gasification fine slag content on the hydration products of the paste is as follows Fig.11 .

[0030] Table 4 Due to the poor mechanical properties of C3, C3 was not considered in subsequent tests. From the heat release rate curve, it can be observed that the heat release rate of the pure paste has peaks at two locations. The first peak is caused by the wetting, dissolution and surface energy release of cement and coal gasification fine slag particles, and occurs immediately after water comes into contact with cement and coal gasification fine slag. The second peak appears at around 4-16 h. The rapid heat release in this stage is related to the precipitation of hydration products, so it can also reflect the amount of hydration products generated in the pure paste in the early stage of hydration. Figure 7 It can be seen that with the increase of coal gasification slag content, the second peak value gradually decreases, and the second peak values ​​of C1 and C2 are about 9% and 20% lower than that of C0, respectively. This indicates that the amount of hydration products generated in the early stage of the paste is reduced, and it also explains the reason why the early mechanical properties of the mortar are poor. In addition, with the increase of coal gasification slag content, the induction period of the paste is significantly extended. Since the induction period is usually related to the setting time of the paste, the addition of coal gasification slag delays the setting and hardening of cement.

[0031] As the amount of coal gasification fine slag increases, the cumulative heat release of the pure paste gradually decreases. The cumulative heat release of C1 and C2 decreases by about 6% and 24% compared with C0, respectively. As the amount of coal gasification fine slag increases, the decrease in the cumulative heat release increases significantly, indicating that high amounts of coal gasification fine slag have a strong inhibitory effect on cement hydration reaction.

[0032] The Krstulovic-Dabic hydration kinetic model was used to further analyze the hydration process of the pure slurry in combination with the hydration heat data. The hydration process is divided into three stages: nucleation and crystal growth (NG), phase interface (I) and diffusion (D), and each stage is considered to be independent of each other.

[0033] The calculation process is as follows: Differentiation process: Where n, K NG , K I , K D is the hydration kinetic parameter, obtained by curve fitting of equations (1)-(3); α represents the degree of hydration, calculated by the following formula: In the formula, QMax is the theoretical cumulative heat release, calculated using the following formula: Where Q(t) is the heat released by the slurry from the hydration acceleration period to time t; 50 It is the time when the cumulative heat release reaches half of the theoretical cumulative heat release; t0 is the time when the induction period ends or the acceleration period begins.

[0034] Figure 8 The hydration rate curve and simulation results of the pure paste are given. The model can accurately simulate the hydration process of C0, indicating that the cement used in this study is suitable for this model. At the same time, the model accurately simulates the NG and D processes of C1, but there is an obvious error in the I process. The model has a poor simulation effect on any process of CS2, which shows that the hydration behavior of the pure paste under a high amount of coal gasification fine slag is significantly different from that of pure cement. Table 4 shows the hydration kinetic parameters of the pure paste. Among them, n reflects the crystallization nucleation and crystal growth of the hydration product. With the increase of the amount of coal gasification fine slag, n gradually increases, indicating that the coal gasification fine slag helps to improve the nucleation and crystal growth of the hydration product, which is due to the nucleation effect of the coal gasification fine slag. K of the pure paste NG The value of ' is about K I ', about 4 times K D ', indicating that the hydration reaction of the pure pulp is mainly controlled by the NG process. I 'It decreases with the increase of coal gasification fine slag content because the concentration of calcium hydroxide decreases with the increase of coal gasification fine slag content, and the volcanic ash reaction rate of coal gasification fine slag is reduced. When the coal gasification fine slag content is 10%, K D ' increases, when the dosage increases to 30%, K D 'Decrease. After adding a small amount of coal gasification slag, the amount of hydration products in the pure slurry is reduced, and the ion diffusion resistance is reduced; for the pure slurry with a high amount of coal gasification slag, the coal gasification slag significantly changes the hydration exothermic behavior of the pure slurry, and the hydration kinetic parameters may have a large error. On the other hand, a large amount of organic matter in the coal gasification slag may also hinder ion diffusion.

[0035] Since the content of coal gasification fine slag in C1 is low, no significant changes may be observed when analyzing its hydration products. Therefore, XRD tests were conducted on C0 and C2. The results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that the main hydration products in the pure paste are calcium sulfonate, monosulfate, hemicarbonate, monocarbonate and calcium hydroxide. As the curing time increases, the diffraction peak intensity of C2S and C3S decreases, indicating that cement hydration continues during the curing period. Among the hydration products of C0, calcium sulfonate and hemicarbonate have a higher crystallinity. This is because pure cement is rich in sulfates, which can react with aluminates to form calcium sulfonate. For C2, due to the high content of Al2O3 in the coal gasification fine slag and the similar content of SO3 to cement, this will lead to excessive aluminates and insufficient sulfates in the pure paste, thereby inducing the phase transition of calcium sulfonate to monosulfate. Therefore, the diffraction peak of calcium sulfonate in C2 is almost invisible.

[0036] For C0, the diffraction peak of calcium hydroxide gradually increases with the increase of curing time. This is because calcium hydroxide is one of the hydration products of C2S and C3S, as shown in equations (10) and (11). The hydration reaction in the pure cement system does not consume calcium hydroxide, so with the extension of curing time, the intensity of the diffraction peak of calcium hydroxide gradually increases.

[0037] Different from C0, in addition to the above reactions, the active silicon in the coal gasification fine slag reacts with calcium hydroxide to form additional CSH gel in C2, as shown in formula (11). Therefore, with the increase of curing time, the crystallinity of calcium hydroxide in C2 gradually decreases.

[0038] Fig.10 The SEM images of C0 and C2 after 28 days of curing are shown. Dense flaky calcium hydroxide formed by the hydration of C2S and C3S can be observed in C0, and the microstructure of C0 is obviously more dense. A large number of unhydrated coal gasification fine slag particles and porous carbon that cannot participate in the hydration reaction can be observed in C2. In addition, these particles and porous carbon cannot fit tightly with the hydration products, resulting in the formation of a large number of pores and cracks. The large number of pores and cracks is also one of the main reasons for the poor mechanical properties of mortar with high coal gasification fine slag content.

[0039] In order to gain a deeper understanding of the effect of coal gasification fine slag content on cement paste hydration products, GMES software was used to analyze the hydration products of cement paste. Fig.11. When the coal gasification fine slag content is 0%, the main hydration products are CSH gel, calcium hydroxide, calcium sulfonate, monosulfate and hydrotalcite. Except for hydrotalcite, the other hydration products are consistent with the XRD results after 28 days of C0 curing, indicating that the established cement phase is reliable. The reason why hydrotalcite was not observed may be that the content of MgO in cement is low, resulting in poor crystallinity of hydrotalcite. The coal gasification fine slag phase is established based on its chemical composition, mineral composition and carbon content, of which about 28% is completely unable to participate in the hydration reaction. With the increase of the coal gasification fine slag content, the content of calcium hydroxide and calcium sulfonate gradually decreases, and the content of CSH gel and calcium sulfonate gradually decreases, which is consistent with the observation in XRD. In the case of complete reaction, when the coal gasification fine slag content is 30%, the calcium hydroxide formed by cement hydration can be completely consumed, so 30% can be considered as the theoretically optimal coal gasification fine slag content. However, complete hydration requires a long reaction time, and curing for 28 days is far from meeting the requirements of complete hydration. In addition, the organic components in coal gasification slag will hinder cement hydration and affect the formation and crystallization of hydration products. Therefore, the diffraction peak of calcium hydroxide is still observed in XRD. Although there are differences between the simulation results and the measured values, it still shows that coal gasification slag can consume calcium hydroxide and induce the phase transition of calcium sulfonate. When the content of coal gasification slag reaches 50%, a large number of unreacted coal gasification slag particles will exist in the system, inducing the formation of pores and cracks, and at this time the content of CSH gel is significantly reduced, so its mechanical properties are greatly reduced.

[0040] In summary, the embodiment of the present invention provides a method for improving the performance of mortar by using coal gasification slag as an auxiliary cementitious material. It can be seen that: 1) The addition of coal gasification slag can significantly reduce the fluidity of mortar, and the greater the addition amount, the greater the decrease in fluidity; in terms of setting time, the addition of coal gasification slag can prolong the setting time of neat mortar, but the effect is not significant when the addition amount is small (10%); in terms of mechanical properties, the addition of coal gasification slag significantly reduces the early flexural / compressive strength of mortar. After 28 days of curing, the compressive strength of mortar with 10% coal gasification slag is equivalent to that of pure cement.

[0041] 2) The addition of coal gasification fine slag reduces the hydration heat of the paste and has a significant delaying effect on cement hydration; coal gasification fine slag is beneficial to the crystallization nucleation and crystal growth process of cement, but is not conducive to the phase boundary reaction and diffusion process; when the addition amount of coal gasification fine slag is 50%, its hydration mechanism changes slightly, and the applicability of the Krstulovic-Dabic hydration kinetic model is poor.

[0042] 3) The main hydration products in the pure slurry are ettringite, monosulfate, hemicarbonate, monocarbonate and calcium hydroxide. The addition of coal gasification fine slag consumes calcium hydroxide and increases the content of CSH gel in the system. In addition, coal gasification fine slag also induces the phase change of ettringite. The theoretical optimal dosage of coal gasification fine slag is 30%.

[0043] The present invention uses coal gasification fine slag as an auxiliary cementitious material. The smaller the mortar fluidity, the greater the viscosity; the greater the mortar fluidity, the lower the viscosity. Therefore, the largest possible dosage is required. The larger the dosage, the lower the flowability and the greater the viscosity. However, if the dosage is too large, the flowability and mechanical properties will decrease. In order to prevent the mechanical properties from decreasing too much, the dosage needs to be controlled, that is, the optimal dosage is 30%.

[0044] The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be determined that the specific embodiments of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the present invention, which should be regarded as belonging to the present invention and the scope of patent protection determined by the submitted claims.

Claims

1. A mortar with improved overall performance based on coal gasification fine slag, characterized in that: It includes 11-20wt% of cement, 58-75.8wt% of standard sand and 2.2-11.1wt% of coal gasification fine slag.

2. The mortar with improved overall performance based on coal gasification fine slag according to claim 1, characterized in that: The mass percentage content of carbon in coal gasification fine slag is 23.41%.

3. The mortar with improved overall performance based on coal gasification fine slag according to claim 1, characterized in that: The cement is silicate PI42.5 standard cement.

4. A method for preparing mortar with improved overall performance based on coal gasification fine slag as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Treatment of coal gasification fine slag: Dry the coal gasification fine slag at 100-110°C to constant weight, and sieve it using a 180-200 mesh sieve; S2, weigh 2.2-11.1wt% of coal gasification fine slag, add 11-20wt% of cement, 58-75.8wt% of standard sand and water to dilute and stir to form a coal gasification fine slag slurry with a solid mass fraction of 88-89wt%; the coal gasification fine slag, standard sand and cement are all amorphous, and the particle size is less than 110μm; S3. The coal gasification fine slag slurry is fully stirred and introduced into a screening device, and the large-particle solid components are separated through a 200-400 mesh sieve, and the separated slurry under the sieve is collected to obtain a composite slurry.

5. The method for preparing mortar with improved overall performance based on coal gasification fine slag according to claim 4, characterized in that: The stirring in step S2 is carried out at room temperature using a high-speed disperser, with a stirring speed of ≥1500r / min and a stirring time of ≥30min.

6. A method for preparing mortar based on coal gasification fine slag to improve overall performance according to claim 5, characterized in that: The stirring time in step S2 is ≥1.5h.

7. The method for preparing mortar with improved overall performance based on coal gasification fine slag according to claim 4, characterized in that: The rotation speed of the sufficient stirring described in step S3 is 1800~3000r / min, and the stirring time is 30~120min.

Citation Information

Patent Citations

  • Method for preparing cement admixture, cement admixture and cement composition

    CN107857499A

  • Antiskid material and road surface treatment method using same

    CN116813241A

  • Cement additive material and cement composition

    JP2019014640A

  • High Early Cement Composition for Road Pavement and Pavement Method Using Thereof

    KR101904172B1

  • Method for manufacturing of supplementary cementitious materials (SCMS)

    US20130233208A1